The use of co-design in developing physical activity interventions for older adults: a scoping review protocol. Issue 2 (7th February 2022) - Edward, Holly; Constantin, Natalie; Ng, Hayley; Radisic, Anna; D'Asti, Alina; Yule, Amy; D'Amore, Cassandra; Reid, Julie C.; Beauchamp, Marla
ABSTRACT: Objective: The objective of this scoping review is to map the available evidence on the use of co-design in developing physical activity interventions for older adults. Introduction: Remaining physically active throughout life is important for maintaining independence and quality of life. Co-design is an effective way to engage end users in health-related policy development and health care interventions; however, the definition and operational use of co-design varies widely. This scoping review will summarize the available evidence on how co-design is used to engage older adults in physical activity interventions and identify areas for future research. Inclusion criteria: Studies must have at least one participant aged 60 years or older and include concepts related to co-design and physical activity to be eligible for inclusion. Eligible studies must be original, peer-reviewed research. Methods: MEDLINE, Embase, CINAHL, and AMED databases will be searched from inception to February 18, 2021. Following duplicate removal, titles and abstracts will be screened and selected according to predefined inclusion criteria by two or more independent reviewers. Kappa level of agreement will be calculated between reviewers for selection of titles and abstracts. The remaining full texts will be screened against inclusion criteria, and reasons for exclusion will be reported. Data will be extracted from included studies by two or more independent reviewers according to the Participant, Concept, Context framework. Information pertaining to the aims of this scoping review and the study methodology will be extracted and presented in tabular format, accompanied by a narrative summary. Scoping review registration number: Open Science Framework Registration (osf.io/vsw2m)